Subjective Perception of Violence: How Teachers Understand Violence Against Them - Penkauskienė, Daiva; Indrašienė, Valdonė; Railienė, Asta; Sadauskas, Justinas; Merfeldaitė, Odeta; Jegelevičienė, Violeta; Prakapas, Romas; Diržytė, Aistė; Bitinaitė- Motiejūnienė, Rugilė; Pivorienė, Jolanta (Social Welfare: Interdisciplinary Approach, 2026)
There is a lack of research analyzing how teachers themselves define violence and what patterns of behavior they personally consider to be violent. It is precisely this subjective perception of violence that may explain why some situations remain invisible at the institutional level: they are not named and reported, or they are normalized as part of a teacher’s job, even though, in the long run, they can negatively affect a teacher’s professional identity and well-being. A phenomenographic perspective was applied in this research. It has been found that teachers understand violence in the workplace as pressure to obey, aggressive behavior, insults, public humiliation, and non-transparent decisions, which are characterized by verbal, physical, written, and visual expressions. The scope of the research results shows that the teachers’ perception of violence is not limited to incidents but is revealed as a process of constructing meaning that combines the form of violence, structural features, and orientation toward the teacher as a professional or as a person. The study broadens not only the concept of violence in the school environment but also the field of analysis of the teacher as an object of violence, and it reveals that the teachers’ understanding of violence is more related to administrative power practices.